7 - The socio-economic well-being of internal migrants in Agbogbloshie, Ghana - Ronald Adamtey; John Ebotui Yajalin; Charles Yaw Oduro (African Sociological Review, 2015)
The recent claims that migration can improve the well-being of migrants and thei dependants back home has mainly focused on international migration to destinations that are considered developed. Few studies have focused on internal migration and its effects on migrants’ wellbeing. Besides, whether migrations to areas that are considered not developed can also contribute to improving the well-being of migrants and their dependants back home remains unaccounted for in the literature. This study employed a quantitative design involving descriptive statistics, independent t- test and binomial test to examine the effects of internal migration on the wellbeing of migrants in Agbogbloshie-the most populous slum in Accra. The study found that the determinants of well-being; income, education and employment have improved for migrants after migration. The results implied that migration had a net positive effect on migrants’ wellbeing. However, this benefit comes at a cost as migrant workers are engaged in works that post a lot of risk such as carrying very heavy loads, exposed to toxic substances and living in very poor accommodation. The paper recommends that efforts be made by governments to bridge the development gap between the north and south of the country so as to limit the rate of migration